2022
DOI: 10.3390/ijms23073710
|View full text |Cite
|
Sign up to set email alerts
|

Histamine Causes Pyroptosis of Liver by Regulating Gut-Liver Axis in Mice

Abstract: Huangjiu usually caused rapid-drunkenness and components such as β-benzyl ethanol (β-be), isopentanol (Iso), histamine (His), and phenethylamine (PEA) have been reported linked with intoxication. However, the destructive effect of these components on gut microbiota and liver is unclear. In this study, we found oral treatment of these components, especially His, stimulated the level of oxidative stress and inflammatory cytokines in liver and serum of mice. The gut microbiota community was changed and the level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In addition, YEH was able to reduce the content of histamine in this pathway, which mediates GI tract damage that is induced by alcohol ( Zimatkin and Anichtchik, 1999 ). Studies in mouse models have found that the oral administration of histamine can cause gut microbiota disorder, oxidative stress, inflammatory response ( Luo et al, 2022 ), and cause liver fibrosis ( Kennedy et al, 2020 ). In morphine addiction and cGMP-PKG signaling pathways, high doses of yeast extract modulate both pathways by reducing the levels of adenosine and 5′ -adenine nucleotide ( Figure 7B ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, YEH was able to reduce the content of histamine in this pathway, which mediates GI tract damage that is induced by alcohol ( Zimatkin and Anichtchik, 1999 ). Studies in mouse models have found that the oral administration of histamine can cause gut microbiota disorder, oxidative stress, inflammatory response ( Luo et al, 2022 ), and cause liver fibrosis ( Kennedy et al, 2020 ). In morphine addiction and cGMP-PKG signaling pathways, high doses of yeast extract modulate both pathways by reducing the levels of adenosine and 5′ -adenine nucleotide ( Figure 7B ).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of bile acid in the intestine contributes to a normal gut barrier function by promoting intestinal epithelial cell proliferation. In biliary obstruction, intestinal mucosal injury is mainly due to more LPS caused by intestinal flora disorder ( Assimakopoulos et al, 2007 ; Luo et al, 2022 ). To further confirm the effect of OCA on the proliferation and apoptosis of intestinal mucosal epithelial cells, Caco2 cells were incubated with LPS and OCA in vitro .…”
Section: Resultsmentioning
confidence: 99%
“…Pearson’s correlation analysis showed that the relative abundance of microbiota relating to liver pyroptosis, e.g., Parabacteroides , Bacteroides , Lactobacillus , and Alistipes , were increased significantly in AFB 1 -treated mice, as well as in the transplanted group. Several lines of evidence indicated that Parabacteroides , Bacteroides , and Alistipes could activate NLRP3 signaling. The variation of these gut bacteria is consistent with the activation of liver pyroptosis, indicating that they could be the key factors to promote liver pyroptosis.…”
Section: Discussionmentioning
confidence: 99%